Factors Affecting the Smoking Rate of Cigarettes Among Adolescents - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study aimed to investigate the factors affecting the smoking rate of regular cigarettes among adolescents in one region of Korea. The ‘smoking rate,’ ’smoking experience rate,’ ’current smoking rate,’ and ’daily smoking rate’ for cigarettes were investigated. Smoking probability was calculated according to the presence or absence of smokers in the family, presence or absence of secondhand smoke in the home, presence or absence of witnessing smoking by faculty and staff, presence or absence of secondhand smoke in the school, and experience of secondhand smoke excluding home and school. For the analysis of the results, an odds ratio was calculated using a logistic regression analysis. This study found that, having a smoker in the family, experience of secondhand smoke at home, witnessing smoking by faculty members, and experience of secondhand smoke in school were significant influencing factors.